Programmable Amplitude‐Coding Metasurface with Multifrequency Modulations. (7th May 2021) - Hong, Qiao Ru; Ma, Qian; Gao, Xin Xin; Liu, Che; Xiao, Qiang; Iqbal, Shahid; Cui, Tie Jun
Abstract : Recently, programmable metasurfaces have aroused great attention for various applications such as beam manipulation, wireless communication, and holograms by modulating the spatial phase or amplitude. However, programmable amplitude‐coding modulations have rarely been investigated due to the difficulty in realizing dynamic control of amplitude. Herein, a real‐time programmable amplitude‐coding metasurface with multifrequency modulation is proposed by integrating PIN diodes and chip attenuators to the metaelement. The element is encoded as "11, " "10, " and "00, " corresponding to the ON/OFF states of two diodes. By switching the two states of the PIN diode, the metaelement exhibits distinctly reflected amplitude responses in three frequencies (2.98, 4.11, and 5.73 GHz). For the whole metasurface, the magnitude of the reflected beam can be modulated with some specific coding patterns. To verify the performance, six coding patterns with 10 × 10 metaelements are designed, and four of them are measured. Experimental results are fundamentally consistent with theoretical designs and simulations. Further a wireless communication demonstration is designed and implemented to perform direct modulation of digital signals without using mixers required in the conventional wireless communication systems. It is envisioned that this work will find applications in new architecture encrypted communication and imaging systems. Abstract : A real‐time programmable amplitude‐coding metasurface with multifrequency modulation is proposed by integrating PIN diodes and chip attenuators to the metaelement. By switching the PIN diodes, the metaelement exhibits distinct amplitude responses in three frequencies. A wireless communication demonstration is designed and implemented to perform direct modulation of digital signals without using the mixers required in the conventional wireless communication systems.